Effectiveness of Empowerment-Based Diabetes Education on Diabetes Complication Prevention: A Systematic Review - Rondhianto Rondhianto; Siswoyo Siswoyo; Ahmad Fathoni (Universitas Aisyah Pringsewu, 2022)
Diabetes mellitus is a chronic metabolic disease that requires continuous medical management and good self-care behavior. Failure in self-management will lead to complications and an increased risk of death. However, most patients do not have good self-management. One strategy to improve self-management is to conduct empowerment-based education, but its effectiveness is still unclearly. This study aims to identify the effectiveness of empowerment interventions in preventing diabetes complications. This study is a systematic review using the PRISMA protocol and JBI Critical Appraisal Tools to determine eligible articles. The articles search from five databases (PubMed, ProQuest, Science Direct, Google Scholar, and ClinicalKey for Nursing). The inclusion criteria were English, published 2012 - 2022, and experimental study. The study result showed that empowerment education could significantly increase knowledge and skills in people with diabetes so that patients can carry out self-management well, including HbA1c management, drug management, physical activity management, and diet management. Effective empowerment education interventions can reduce complications through increasing self-care behavior in diabetics, so educational interventions with empowerment can be used as an effort to prevent complications in people with diabetes mellitus. Abstrak: Diabetes melitus merupakan penyakit metabolik kronik yang membutuhkan tatalaksana medis dan perilaku perawatan diri yang baik secara berkelanjutan. Kegagalan dalam pengelolaan mandiri akan menyebabkan komplikasi dan peningkatan resiko kematian, namun demikian sebagian besar penderita tidak memiliki pengelolaan mandiri dengan baik. Salah satu strategi untuk meningkatkan pengelolaan mandiri yaitu melakukan edukasi berbasis pemberdayaan, tetapi terkait dengan kefektivitasanya belum diketahui dengan pasti. Penelitian ini bertujuan untuk mengidentifikasi efektivitas intervensi pemberdayaan dalam mencegah komplikasi diabetes. Metode penelitian ini adalah systematic review dengan PRISMA protokol dan JBI Critical Appraisal Tools untuk menentukan artikel yang eligible. Database yang digunakan adalah Pubmed, ProQuest, Science Direct, Google Scholar, dan ClinicalKey for Nursing. Studi diterbitkan dalam Bahasa Inggris pada tahun 2012-2022 dengan tipe penelitian eksperimen. Hasil analisis studi menunjukkan bahwasanya edukasi pemberdayaan secara signifikan dapat meningkatkan pengetahuan dan keterampilan pada penderita diabetes, sehingga pasien mampu melakukan manajemen diri dengan baik meliputi manajemen HbA1c, manajemen obat, manajemen aktivitas fisik, dan manajemen diet. Intervensi edukasi pemberdayaan efektif dapat menurunkan komplikasi melalui peningkatan perilaku perawatan diri pada penderita diabetes, sehingga intervensi edukasi dengan pemberdayaan dapat digunakan sebagai upaya pencegahan komplikasi pada penderita diabetes